2017 European guideline for the management of pelvic inflammatory disease. (February 2018) - Ross, Jonathan; Guaschino, Secondo; Cusini, Marco; Jensen, Jorgen
The European guideline for the management of pelvic inflammatory disease includes evidence-based advice on the investigation and treatment of pelvic inflammatory disease (PID). It has been updated to acknowledge the role of Mycoplasma genitalium as an important cause of PID with testing now recommended for women presenting with possible PID and for the male partners of women with confirmed M. genitalium infection. Recent evidence suggests that serious adverse events are uncommon when using moxifloxacin and its use is now recommended as a first-line therapy, especially in those women with M. genitalium PID. The potential utility of MRI scanning of the pelvis in excluding differential diagnoses has been highlighted. The use of doxycycline is now suggested as empirical treatment for male partners of women with PID to reduce exposure to macrolide antibiotics, which has been associated with increased resistance in M. genitalium .